EFFECTS OF FENSID AND FENSID PREMIX ON HEMATOLOGICAL BLOOD PARAMETERS IN CHICKENS WITH MIXED EIMERIOSIS AND COLIBACILLOSIS - Davletbayevna, Ibragimova Feruza (Research Focus International Scientific Journal, 2026)
This scientific article investigates the effects of Fensid and Fensid Premix on hematological blood parameters in chickens under conditions of mixed eimeriosis and colibacillosis. The study was conducted on ROSS 308 broiler chicks, and the dynamics of erythrocytes, leukocytes, hemoglobin, and thrombocytes were analyzed.